Ensuring value for money in public procurement: A case study of Koforidua Polytechnic - Ademan, Frank T. (2015)
A thesis submitted to the school of graduate studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the degree of Master of Science in procurement management